UPAYA SEKOLAH DALAM PEMBINAAN SIKAP NASIONALISME SISWA DI SMPN 3 PRINGGABAYA - Solleha, Gawi Reza; Lalu Sumardi; Edy Kurniawansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Nationalism is an attitude or spirit that every Indonesian citizen must have in loving his homeland. The purpose of this study is to determine the strategy of fostering student nationalism attitudes at SMPN 3 Pringgabaya as well as supporting and inhibiting factors of school efforts in fostering student nationalism attitudes. This approach uses a qualitative approach with a case study type of research. Data collection techniques use observation, interview and documentation techniques that are processed and analyzed by condensing data, presenting data and drawing conclusions to answer the problems that have been formulated. Based on the results of the study, the form of school efforts in fostering student nationalism attitudes is carried out through two channels, namely intracurricular and extracurricular activities. So based on the findings of SMPN 3 Pringgabaya made optimal efforts in instilling nationalism attitudes of students.